Textbook of econometrics - "Klein, Lawrence R" (New Delhi, 1975)
Applied econometric analysis is used across many disciplines and in many branches of economics. Increasingly, data is becoming more readily available and software has become more powerful, enabling the analysis of numerous economic phenomenon.
Keywords: Economics